Simulation and Analysis of the Single Drum Dryer Drive System based on Creo - Wu Zhanyuan; Du Zhilong (Jixie chuandong)
The drum dryer is widely applied in various aspects. The drive system of single drum dryer with starching rollers is composed of gear drive and chain drive. The method for the parametric modeling and assembling of the single drum dryer drive system is realized with Creo 3. 0 software. The actual problems of the machine is analyzed by using motion simulation and stress simulation,and the improvement suggestion is proposed,which would have some reference meaning on the designing and optimizing of the whole machine.